Edugame Development: Genius Learn Platformer to Increase Students' Learning Motivation and Learning Outcomes - Yusuf, Ahmad; Hardianto, Deni (UNDIKMA, 2025)
This study aims to develop and test the effectiveness of the “Platformer Genius Learn” edugame to improve students’ motivation and learning outcomes in the Fundamentals of Educational Technology course using the ADDIE development model. This limited trial subject consisted of one class with a total of 26 subjects who were first-semester students of the Educational Technology Study Program at Padang State University. The tools used in this study included validation sheets for subject matter experts and media experts, student learning motivation questionnaires, and pre-test and post-test assessments to measure the results.The results of the study show: 1) edugame: Platformer Genius Learn Suitable for use based on media expert validation showing an average score of 4.13 in the